Leading Multi-Generational Workforce for Environmental Innovation: Bridging Gen Z, Millennial, and Gen X Perspectives in Sustainable Organizations - Munawir, Muhamad Anang; Bukhori, Reza Fauzi; Salam, Fadlan Abdilah (KarismaPro, 2025)
. This research examines how multi-generational leadership approaches can enhance environmental innovation in Indonesian organizations. With workplaces increasingly comprising Gen Z (digital natives with strong environmental consciousness), Millennials (purpose-driven professionals), and Gen X (experienced leaders with institutional knowledge), understanding generational differences becomes critical for sustainable organizational transformation. Through mixed-method research involving 1,200 employees across 40 Indonesian organizations, this study analyzes how different generational perspectives contribute to environmental innovation initiatives. Key findings reveal that Gen Z brings technological innovation and sustainability urgency (contributing 47% of green innovation ideas), Millennials excel at collaborative implementation and stakeholder engagement (leading 63% of successful sustainability projects), while Gen X provides strategic oversight and resource allocation expertise. The research proposes the Multi-Generational Environmental Leadership Framework (MGELF), which integrates generational strengths to accelerate sustainable organizational transformation. Results show organizations implementing this framework achieved 34% higher environmental performance scores and 28% better employee engagement in sustainability initiatives compared to traditional single-generation leadership approaches.